Profile of the gut microbial composition in Apis mellifera larvae collected in Ha Noi - Dong, Van Quyen; Bui Thi , Thuy Duong; Pham, Thi Lanh; Nguyen, Thi Hoa; Nguyen, Quang Huy; Ha, Thi Thu; Pham, Hong Thai (Academia Journal of Biology, 2024)
The gut microbiota plays a crucial role in food digestion, enhances the host's immune system, and against pathogens. Numerous studies have been conducted on the microbiota of insects in general and honeybees in particular. However, studies have primarily focused on adult honeybees, with fewer studies dedicated to larvae. Despite being within the hive, honeybee larvae still possess their distinct microbiota. To gain a deeper understanding of the microbiota in the larvae of Apis mellifera honeybees, the larva from honeybee colonies collected in Ha Noi, Vietnam was investigated. Next-generation sequencing (NGS) targeting the 16S rRNA gene was employed for microbiome analysis. Results revealed the presence of 5 phyla including Proteobacteria (70.43%), Actinobacteria (1.16%), Firmicutes (20.87%), Bacteroidetes (2.72%), and Chloroflexi (2%). Representative genera included Bombella (29.97%), Lactobacillus (14.91%), Gilliamella (9.59%), Frischella (4.69%), Snodgrassella (3.85%), and Marinobacter (1.21%). Further characterized species composition in the sample we identified the prevalence of Bifidobacterium intestini (29.96%), Gilliamella apicola (8.08%), Frischella perrara (4.55%), Lactobacillus kimbladii (2.85%), Lactobacillus plantarum (2.80%), Snodgrassella alvi (2.77%), Lactobacillus mellis (2.59%), Lactobacillus_uc (unclassified or not yet classified to species, 2.19%), Lactobacillus kunkeei (1.43%), and Lactobacillus melliventris (1.31%). Understanding these microbial dynamics is crucial for developing strategies to support honeybee health and mitigate the challenges posed by factors, such as pesticides, environmental pollution, and honeybee diseases.